Administracja gospodarcza w warunkach Unii Europejskiej - Kiczka, Karol (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
This article offers an analysis of current Polish economic administration under a new situation resulting from the establishment and operation of the European Union. Economic administration is an element of a public authority system, and its functions and place in society are determined by legal order. Poland’s membership in the European Union, together with the previous adjustment period, has considerably changed our economic administration. This analysis concludes that the impact of the Union acquis on Polish economic administration is a process which should be carefully observed by academics and practitioners alike.
Keywords: European Union; economic administration